Amplifying Apoptosis Homing Nanoplatform for Tumor Theranostics. Issue 14 (10th May 2018) - Zhao, Heng; Zhou, Ping; Huang, Kai; Deng, Guang; Zhou, Zhiguo; Wang, Jing; Wang, Mingwei; Zhang, Yingjian; Yang, Hong; Yang, Shiping
Abstract: Nanomedicine has significantly impacted cancer theranostics. However, its efficiency is restricted by the limited enhanced permeability and retention effect of nanomaterials and insufficient density/specificity of receptors of tumor cells. Herein, an apoptosis‐homing nanoplatform based on zinc(II) dipicolylamine (ZnDPA) conjugated Fe/Fe3 O4 nanoparticles (MNPs/ZnDPA), which demonstrates amplified magnetic resonance signal and photothermal therapy, is developed. In an apoptotic xenograft model constructed by doxorubicin, due to the high affinity between ZnDPA and the upregulated level of phosphatidylserine on the outer surface of apoptotic cancer cells, the accumulation value of MNPs/ZnDPA is enhanced two‐fold and the tumor/muscle ratio of T 2 values is decreased to 50% compared to that in the normal xenograft model. In the apoptotic xenograft model, the amplifying photothermal therapy is confirmed by the changes of the relative tumor volume and terminal deoxynucleotidyl transferase‐mediated dUTP‐biotin nick end‐labeling staining. This nanoplatform provides a promising strategy to improve the targeting efficiency of nanoparticles and the enhancement of tumor‐targeting theranostics. Abstract : Zinc(II) dipicolylamine (ZnDPA) conjugated Fe/Fe3 O4 nanoparticles (MNPs/ZnDPA) are developed for the amplifying magnetic resonance imaging and photothermal therapy in the apoptotic 4T1 xenograft model.